Aerospace Marketing Management A Handbook for the Entire Value Chain - Malaval, Philippe; Bénaroya, Christophe; Aflalo, Jonathan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book presents an overall picture of both B2B and B2C marketing strategies, concepts and tools, in the aeronautics sector. This is a significant update to an earlier book successfully published in the nineties which was released in Europe, China, and the USA. It addresses the most recent trends such as Social Marketing and the internet, Customer Orientation, Project Marketing and Con current Engineering, Coopetition, and Extended Enterprise. Aerospace Marketing Management is the first marketing handbook richly illustrated with executive and expert inputs as well as examples from parts suppliers, aircraft builders, airlines, helicopter manufacturers, aeronautics service providers, airports, defence and military companies, and industrial integrators (tier-1, tier-2). This book is designed as a ready reference for professionals and graduates from both Engineering and Business Schools.
1. Marketing in the aeronautics industry -- 2. The Individual and Organizational Purchase -- 3. Business Marketing Intelligence -- 4. Market Segmentation and Positioning -- 5. Marketing and Sales Action Plan -- 6. Innovation and Product Management -- 7. Marketing of Services -- 8. Pricing Policy -- 9. Selecting Distribution Channels and Sales Team Management -- 10. Project Marketing -- 11. Communication Policy -- 12. Selecting Media -- 13. Brand Management -- 14. Building Loyalty: Maintenance, Customer Training and Offsets -- 15. Alliance Strategies.
Keywords: Marketing; Aerospace engineering; Astronautics; Production management; Transportation; Project management; Marketing; Aerospace Technology and Astronautics; Operations Management; Transportation; Project Management